How to make injection molds - Menges, George, (Hanser Publishers, 1993)
Materials for injection molds -- Mold making techniques -- Procedure for estimating mold costs -- The injection molding process -- Design of runner systems -- Design of gates -- Venting of molds -- Ejection -- Computer asisted mold design -- Temperature controllers for injectionand compression molds